Impact of the teaching for understanding (TFU) approach on the academic performance of secondary school students at “Hermanas Bethlemitas Sagrado Corazón de Jesús” School - Pamplona (2020)
The objective of this article is to analyze the incidence of the Teaching for Understanding (TFU) approach in the academic performance of secondary-school students at “Hermanas Bethlemitas - Sagrado Corazón de Jesús” School in Pamplona (Norte de Santander). The type of research used was qualitative with a phenomenological design. The key participants were five students, one in ninth-grade, three in tenth-grade and one in eleventh-grade, who had low academic performance before the implementation of the Teaching for Understanding (TFU) approach and who have improved their results in the following years, according to evaluation commissions; and three teachers from the areas of English, Mathematics and Biology. For data collection, individual in-depth interviews and focus group interviews were conducted.The main result is that the Teaching for Understanding approach does not establish a significant degree of impact on the academic performance of students, as is their personal decision regarding academic responsibility, but the methodological change has indeed generated greater involvement. in the classes, feedback, a better student - teacher relationship and with it better results.